The (w)hole story: Facilitation of dead wood fauna by bark beetles?. (April 2016) - Zuo, Juan; Cornelissen, Johannes H.C.; Hefting, Mariet M.; Sass-Klaassen, Ute; van Logtestijn, Richard S.P.; van Hal, Jurgen; Goudzwaard, Leo; Liu, Jin C.; Berg, Matty P.
Abstract: Facilitation between species is thought to be a key mechanism in community assembly and diversity, as certain species create microhabitats for others. A profound characteristic of forest ecosystems is a large amount of dead wood which is colonised by a vast array of invertebrate species. Bark beetles (Scolytinae) feed and breed on dying or dead trees, puncturing holes into the bark and engraving inner bark and outer wood with their galleries. These holes and galleries might facilitate other invertebrates by providing access to the inner bark for shelter, feeding and reproduction. We tested this hypothesised facilitative interaction during the early decomposition phase of coarse woody debris of spruce ( Picea abies L. Karst.) incubated in two environmentally contrasting forest sites in the 'common garden' experiment LOGLIFE. We sampled invertebrates in 25 cm diameter logs at different degrees of colonisation by bark beetles. Our results indicated that (1) bark beetles facilitated the entrance into spruce logs of other invertebrates with body width that matched the size of bark-beetle holes, and (2) the abundance of invertebrates was often positively related to the proportional surface area of inner bark consumed by bark beetles, but more so in the nutrient-rich site than in the nutrient poor site. This study provides the first quantitative test of facilitation between invertebrate clades in dead wood communities. Including facilitative interaction in community assembly studies may change some predictions about relationships between tree functional traits and invertebrate diversity and will lead to a more accurate and comprehensive understanding of dead wood communities. Highlights: Facilitation has rarely been studied in community assembly of detrital systems. Bark beetles facilitate the entrance of macrodetritivores into logs via bark holes. The bark galleries excavated by bark beetles also facilitate macrodetritivores. Including facilitation enhances insight into invertebrate community assembly rules.